グリーンランド氷床表面の積雪融解に対する積雪粒径プロファイルの影響 - 庭野, 匡思; 青木, 輝夫; 的場, 澄人; 山口, 悟; 谷川, 朋範; 山崎, 哲秀; 朽木, 勝幸; 本山, 秀明; Masashi, Niwano; Teruo, Aoki; Sumito, Matoba; Satoru, Yamaguchi; et al. (2013)
In July 2012, extreme surface melt events occurred on the Greenland Ice Sheet (GrIS). Generally, surface melt is physically controlled by the surface energy balance, where net shortwave radiant flux is the main energy source for melt during summer. Although (optically equivalent) snow grain size profile affects near-infrared albedo and in turn net shortwave radiant flux, its qualitative impacts on the surface melt events is unclear. In the present study we investigated effects of snow grain size profile on the surface melt event observed at the site SIGMA-A (78°03’N, 67°38’W, 1,490 m a.s.l.), which locates on northwest part of GrIS, during 30 June to 10 July 2012 through numerical studies with a physically based 1-D snowpack model SMAP. Observed snow physical state at SIGMA-A during 30 June to 13 July is indicated in Figure 1 in terms of snow grain shape profile. As shown in this figure, top melt form layers (depicted with red color) were expanded day by day as a result of surface melt during the period. First of all, we simulated temporal evolution of physical states of near-surface snowpack at SIGMA-A during 30 June to 10 July 2012 by forcing in-situ meteorological data obtained at SIGMA-A. The depth of simulated snow layer, which was characterized by a thick bottom ice formation, was 88 cm on 30 June. The initial states of snowpack were given from the snow pit observation counducted on 30 June 2012, 16:45 UTC. It was found that the simulated shortwave albedo (ctrl in Figure 2) agreed well with measurements (R2 = 0.820, root mean square error = 0.019, and mean error = 0.008). Next, we performed two sensitivity tests with SMAP, where initial snow grain size profile was modulated in order to assess its impacts on the surface energy balance. In these tests we replaced the original snow grain size profile for the top 21 cm melt form layers depicted in Figure 1 (average snow grain size was 0.6 mm) with smaller (test1) and larger profiles (test2). In test1 top 21 cm snow grain size was equally set to be 0.02 mm, ...